Compression after impact studies on composite laminates - Choo, Kenneth Chen Jiang (2014)
The first objective of the project is to find out the influence of core shell polymer (CSP) particles on the impact performance of glass-fiber reinforced polymer (GFRP) composites. The impact properties and damage of GFRP composites toughened with CSP particles were assessed using visual inspection. The second objective of the project is to find out the effect of particle dispersion on the compressive properties of GFRP composites that had undergone impact testing. GFRP composites were first fabricated: some with CSP particles and some without CSP particles. Impact tests were then carried out, and the ultimate compressive strength, maximum loading and Young’s modulus were analyzed. The failure modes were then evaluated through visual inspection. This project will be limited to the use of GFRP composites/epoxy resins with CSP particles dispersed in the ply interfaces. Other types of fiber or resin will not be used. Likewise, alternative particle types will not be used. This project would be largely useful for studying the effect of particle dispersion on the compressive properties of GFRP composites that had undergone impact testing.